1997
DOI: 10.1523/jneurosci.17-06-02056.1997
|View full text |Cite
|
Sign up to set email alerts
|

Proteolipid Protein Regulates the Survival and Differentiation of Oligodendrocytes

Abstract: Proteolipid protein (PLP) has been postulated to play a critical role in the early differentiation of oligodendrocytes (OLs) in addition to its known role as a structural component of myelin.To identify this early function, we blocked the synthesis of PLP in glial cultures with antisense oligodeoxynucleotides that targeted the PLP initiation codon. Primary glial cultures were incubated with phosphorothioate-protected oligodeoxynucleotides (S-ODNs) for up to 11 d. PLP in OLs was reduced Ͼ90%. OLs treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…Additionally at that stage, these cells elaborated large membrane sheaths that mimic the appearance of unfurled myelin sheaths ( Fig. 8C; Yang and Skoff, 1997). Mature oligodendrocytes formed ring structures around distal branches and partly myelinated closely located cells, indicating in vitro myelination.…”
Section: Cultured Oligodendrocytes From Kir41؊/؊ Mice Are Depolarizementioning
confidence: 86%
“…Additionally at that stage, these cells elaborated large membrane sheaths that mimic the appearance of unfurled myelin sheaths ( Fig. 8C; Yang and Skoff, 1997). Mature oligodendrocytes formed ring structures around distal branches and partly myelinated closely located cells, indicating in vitro myelination.…”
Section: Cultured Oligodendrocytes From Kir41؊/؊ Mice Are Depolarizementioning
confidence: 86%
“…In addition to the structural role, PLP might have some nonstructural role (39). It has been suggested that PLP might regulate differentiation and survival of oligodendrocytes (40 Several possible mechanisms could singly or multiply play a role in the VGB-induced delay in myelination and oligodendroglial cell death. First, it is possible that a nonspecific effect such as undernutrition could be involved because poor nutrition is known to disturb myelination (41), and decreased appetite and weight loss have been observed previously with VGB treatment (9,42).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15], and 15 large neurospheres containing Ͼ400 cells (clones nos. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. The panel of individual cDNA libraries from 30 selected clones was generated and normalized.…”
Section: Methodsmentioning
confidence: 99%